2014
DOI: 10.1177/0021955x14524081
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of cell distribution in injection molded microcellular foam

Abstract: The microstructure of cellular materials, in particular microcellular polymers, is commonly characterized by the mean cell size and cell population density. Although the physical properties of foamed polymers are highly dependent on cell distribution, very insignificant work has been carried out to quantify the distribution of cells. This experimental study correlates the influential processing parameters of microcellular injection molding with the cell distribution, mean cell size and population density. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…For quantitatively characterizing polymer foams, Rizvi et al. 13 defined a parameter named “Cell Distribution Index (CDI)” and studied the mean cell size, cell population density, frequency of foamed polystyrene (PS) samples. Using standard ASTM D 638-02 tensile bars, Chandra et al.…”
Section: Introductionmentioning
confidence: 99%
“…For quantitatively characterizing polymer foams, Rizvi et al. 13 defined a parameter named “Cell Distribution Index (CDI)” and studied the mean cell size, cell population density, frequency of foamed polystyrene (PS) samples. Using standard ASTM D 638-02 tensile bars, Chandra et al.…”
Section: Introductionmentioning
confidence: 99%
“…Gómez-Gómez et al [134] reported that the effect of injection speed on the cell density of PETG plates is inconclusive. Rizvi et al [194] pointed out a decrease in cell diameter and CDI parameter with the injection speed. In the present study, the maximum cell size decreased, however, the CDI increased, that is, the cell size distribution became more heterogeneous.…”
Section: Effect Of Injection Speedmentioning
confidence: 99%
“…where n is the number of cells in the micrograph, A is the analyzed area (cm 2 ) and ρs and ρf are the density of solid and foamed material, respectively. The Cell Distribution Index (CDI) was proposed by Rizvi et al [194] to assess the uniformity of cell size distribution, and it is defined as:…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…9 Most of studies have been focused on conventional polymers such as polypropylene, polyethylene or polystyrene. [10][11][12] The relationships between the injection moulding process and the properties were also discussed, but most were limited to the laboratory scale for standardized specimens (simple plate or dog bone specimen). 13,14 Thus, Gong et al 10 reported the effect of cell structure parameters on the mechanical properties of PP materials, which indicated that small and uniform cells result in improvements of the foam tensile and impact strengths.…”
Section: Introductionmentioning
confidence: 99%